Generation and Structuring of Multipartite Entanglement in a Josephson Parametric System. Issue 1 (17th October 2022) - Petrovnin, Kirill Viktorovich; Perelshtein, Michael Romanovich; Korkalainen, Tero; Vesterinen, Visa; Lilja, Ilari; Paraoanu, Gheorghe Sorin; Hakonen, Pertti Juhani
Abstract: Quantum correlations are a vital resource in advanced information processing based on quantum phenomena. Remarkably, the vacuum state of a quantum field may act as a key element for the generation of multipartite quantum entanglement. In this work, generation of genuine tripartite entangled state and its control is achieved by the use of the phase difference between two continuous pump tones. Control of the subspaces of the covariance matrix for tripartite bisqueezed state is demonstrated. Furthermore, by optimizing the phase relationships in a three‐tone pumping scheme genuine quadripartite entanglement of a generalized H‐graph state ( H ∼ $\mathcal {\tilde{H}}$ ‐graph) is explored. This scheme provides a comprehensive control toolbox for the entanglement structure and allows to demonstrate, for first time to the authors' knowledge, genuine quadripartite entanglement of microwave modes. All experimental results are verified with numerical simulations of the nonlinear quantum Langevin equation. It is envisioned that quantum resources facilitated by multi‐pump configurations offer enhanced prospects for quantum data processing using parametric microwave cavities. Abstract : Josephson parametric amplifier under multiple tone pumping scheme provides a comprehensive control toolbox for the generation of multipartite entangled states from the vacuum. Optimization of phase relationships in two‐ and three‐tone pumping schemes produces an advantage for creation of tri‐ and quadripartite genuinely entangled states.